Physical and mechanical properties of fired industrial waste-clay bricks from clam shells and soda lime silica glass - Mohammad, Maryam; Abdul Wahab, Rabiatul Adawiyah; Mazlan, Mazlini; Mohamad Fazil, Nur Nisa Syuhaidah; Ibrahim, Nur Suraya Hanim; Muhamad Nizam, Uswatul Najiha; Abu Hanifah, Ahmad Humaidi; Mohd Zaid, Mohd Hafiz (Elsevier BV, 2023)
Clamshells (CM) and soda lime silica glass (SLS), industrial waste products with superior qualities, were substituted for clay soil (CL) as the primary source of material to create fired industrial waste-clay bricks (FIWCB). They were combined and molded before being fired, and later evaluated for bulk density using dimensional measurement, water absorption, and compressive strength utilizing Rockwell hardness testing equipment. Results revealed the best increase in bulk density, linear shrinkage, and water absorption of the FIWCB with an optimal firing temperature of 1000 °C and SLS addition of 40 % by weight as well as CM addition of 0.15 wt% into the CL.